2016
DOI: 10.1088/0953-8984/28/30/305701
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size scaling in a 2D disordered electron gas with spectral nodes

Abstract: We study the DC conductivity of a weakly disordered 2D electron gas with two bands and spectral nodes, employing the field theoretical version of the Kubo-Greenwood conductivity formula. Disorder scattering is treated within the standard perturbation theory by summing up ladder and maximally crossed diagrams. The emergent gapless (diffusion) modes determine the behavior of the conductivity on large scales. We find a finite conductivity with an intermediate logarithmic finite-size scaling towards smaller conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(150 reference statements)
1
5
0
Order By: Relevance
“…In the past our approach [27] has been compared with experimental work, including the seminal article on graphene by Novoselov et al on graphene [6] and showed good agreement. More recently we also compared our theoretical results for finite-size scaling with experimental results [34], and found excellent agreement. Moreover, we have used two different approaches in this article, namely a functional integral approach based on symmetry considerations (Sect.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…In the past our approach [27] has been compared with experimental work, including the seminal article on graphene by Novoselov et al on graphene [6] and showed good agreement. More recently we also compared our theoretical results for finite-size scaling with experimental results [34], and found excellent agreement. Moreover, we have used two different approaches in this article, namely a functional integral approach based on symmetry considerations (Sect.…”
Section: Discussionsupporting
confidence: 55%
“…Technically, the evaluation of the conductivity contributions for each disorder type does not differ much from the single-cone model evaluation presented in our recent papers Ref. [33,34]. The number of massless modes is obtained by counting zero eigenvalues of the corresponding mass matrices given in Eqs.…”
Section: Conductivity For Different Random Potentialsmentioning
confidence: 99%
See 3 more Smart Citations